PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE (TPS) TERHADAP HASIL BELAJAR SISWA PADA MATERI MENGGUNAKAN ALAT UKUR - Frans Tinus; Debora; Wiyogo (Steam Engineering, 2019)
This study aims to determine the effect of Think-Pair-Share (TPS) learning model on student learning outcomes in using measuring instruments on pneumatic systems lesson. The research methods used are experimental. The sampling technique is random sampling, where the first sample of class X TBSM with the number of students is 32 people, which is taught by the TPS and the second sample class X TBSM with a total of 26 people taught by conventional models, instruments used is a multiple choice test which amounts to 40 questions before the test questions are used to test the validity, reliability, differentiation, and level of difficulty of the questions. The results showed that H0 is rejected and H1 is accepted, which shows that there are influences of student learning outcomes taught using cooperative learning type TPS with student learning outcomes.